2013
DOI: 10.1111/plb.12000
|View full text |Cite
|
Sign up to set email alerts
|

Scent glands in legume flowers

Abstract: Scent glands, or osmophores, are predominantly floral secretory structures that secrete volatile substances during anthesis, and therefore act in interactions with pollinators. The Leguminosae family, despite being the third largest angiosperm family, with a wide geographical distribution and diversity of habits, morphology and pollinators, has been ignored with respect to these glands. Thus, we localised and characterised the sites of fragrance production and release in flowers of legumes, in which scent play… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 76 publications
(107 reference statements)
0
28
0
2
Order By: Relevance
“…Secretory trichomes present in floral organs can produce nectar, volatile and non-volatile oil or sticky substances (Vogel & Machado 1991;Lopes et al 2002;Moyano et al 2003;Marinho et al 2014), contributing to the pollination of the species and its reproductive success. This does not seem to be the case for the floral trichomes of S. bonplandii since their morphology and secretory content are similar to those of the secretory trichomes of leaves.…”
Section: Discussionmentioning
confidence: 99%
“…Secretory trichomes present in floral organs can produce nectar, volatile and non-volatile oil or sticky substances (Vogel & Machado 1991;Lopes et al 2002;Moyano et al 2003;Marinho et al 2014), contributing to the pollination of the species and its reproductive success. This does not seem to be the case for the floral trichomes of S. bonplandii since their morphology and secretory content are similar to those of the secretory trichomes of leaves.…”
Section: Discussionmentioning
confidence: 99%
“…The blends of the BVOCs are usually produced in petal conical cells (Whitney et al 2011) and in scent glands or osmophores during anthesis (Farré-Armengol et al 2013). Marinho et al (2014) localized the sites of fragrance production and release in legume flowers in the perianth and particularly the petals, in which scent plays an important role in pollination. An analysis of cut flower scent in Lathyrus odoratus showed that the aroma was almost exclusively produced by the standard and the wings while the keel petals and other floral parts emitted very little (Sexton et al 2005).…”
Section: General Approach Advertisement and Discoverymentioning
confidence: 99%
“…(Orchidaceae), the trichomes on petals produce non‐volatile oils (Vogel & Machado, ; Blanco et al ., ); and in Anadenanthera peregrina (L.) Speg. (Fabaceae), the petal secretory trichomes produce volatiles (Marinho et al ., ).…”
Section: Introductionmentioning
confidence: 97%